Strategi Penyuluh Agama Islam Dalam Menangkal Faham Radikalisme di Kabupaten Nganjuk - Muhamad Umar Fauzi (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2018)
Extension of Islam is one component of officials who are owned by the Ministry of Religious Affairs in terms of preaching to all levels of society in Nganjuk. Nganjuk district was once thrown by the event of suspected terrorist arrest in Kertosono sub-district. This suggests that a seemingly calm situation in a region can not guarantee that the area is free from radical nests. Therefore, extension agents as the spearhead of the Ministry of Religious Affairs that directly interact with the community at all levels, the role and strategy of extension of Islam is very reliable to prevent the development of radical ideology in Nganjuk district. The approach in this research is deductive and inductive. The type of research used is qualitative research. Researcher is an instrument or tool of research and collect data using observation method, interview, and documentation. The data analysis used is interactive model analysis consisting of; (1). Data reduction (selection of data by theme); (2). Display data (data presentation); and (3). Conclusion / verification. And by examination technique using Trianggulasi. From the research results can be obtained the conclusion that: Extension of Islamic Religion of Nganjuk district amounted to 8 civil servant and 160 Counselor Non-civil servant. There are eight types of specialization of the capability of the established Islamic Counselor. To prevent the development of radical ideology in Nganjuk district, the strategy used is: Placing one counselor of Islam who has competence in the field of Radicalism in every sub-district, Hearings with the authorities to become partners in counseling, Seeking then told to the public about the characteristics and the danger of radical groups,, Strengthening aqidah understanding Ahlusunnah wal Jamaah and instilling love soul of the country, Encouraging people to be active in religious activities held by moderate Islamic organizations.